(untitled) (Práxis Educativa, 2023)
In this article, it is reflected on the concept of ethics in scientific production and publication based on four texts published in the collection of texts entitled Ética e pesquisa em educação: subsídios [Ethics and research in education: subsidies] (volume 1-2019, volume 2-2021) of the National Association of Research and Graduate Studies on Education (ANPEd). Education intellectuals led us to engage in a dialogue on the topic presented by them and the conception of two authors considered classics in History and Philosophy, Aristotle and Thomas Aquinas. In accordance with these sources, we sought to understand to what extent the debate on ethics in research and scientific publication considers the actions of the intellectual person as a human being and not just as an individual of science. The dialogue between formulations by authors from different times and spaces on the subject is possible because our theoretical-methodological path is social history, in which history is a permanent background, as taught by Bloch (2002), and as a long-term process, according to Braudel (2019). We also observe that this study has a bibliographical nature. Keywords: Ethics. Scientific production and publication. ANPEd.